A Textual Processing Model of Risk Communication: Lessons from Typhoon Haiyan - Lejano, Raul P (Archīum Ateneo, 2016)
As the world’s urban poor increase in numbers, they become acutely vulnerable to hazards from extreme weather events. On 8 November 2013, Typhoon Haiyan struck the province of Leyte, Philippines, with casualties numbering in the thousands, largely because of the ensuing storm surge that swept the coastal communities. This study investigates the role and dynamics of risk communication in these events, specifically examining the organizational processing of text within a complex institutional milieu. The authors show how the risk communication process failed to convey meaningful information about the predicted storm surge, transmitting and retransmitting the same routine text instead of communicating authentic messages in earnest. The key insight is that, rather than focus solely on the verbatim transmission of a scripted text, risk communication needs to employ various modes of translation and feedback signals across organizational and institutional boundaries. Adaptation will require overcoming organizational rigidities in order to craft proportionate responses to extreme weather events that may lie outside personal and institutional memory. Future work should build upon the textual processing approach to risk communication, expanding it into a comprehensive relational model of environmental cognition.